Vaccination of cattle with a high dose of BCG vaccine 3 weeks after experimental infection with Mycobacterium bovis increased the inflammatory response, but not tuberculous pathology. (July 2016) - Buddle, Bryce M.; Shu, Dairu; Parlane, Natalie A.; Subharat, Supatsak; Heiser, Axel; Hewinson, R. Glyn; Vordermeier, H. Martin; Wedlock, D. Neil
Summary: A study was undertaken to determine whether BCG vaccination of cattle post-challenge could have an effect on a very early Mycobacterium bovis infection. Three groups of calves ( n  = 12/group) were challenged endobronchially with M. bovis and slaughtered 13 weeks later to examine for tuberculous lesions. One group had been vaccinated prophylactically with BCG Danish vaccine 21 weeks prior to challenge; a second group was vaccinated with a 4-fold higher dose of BCG Danish 3 weeks post-challenge and the third group, remained non-vaccinated. Vaccination prior to challenge induced only minimal protection with just a significant reduction in the lymph node lesion scores. Compared to the non-vaccinated group, BCG vaccination post-challenge produced no reduction in gross pathology and histopathology, but did result in significant increases in mRNA expression of pro-inflammatory mediators (IFN-γ, IL-12p40, IL-17A, IRF-5, CXCL9, CXCL10, iNOs, and TNF-α) in the pulmonary lymph nodes. Although there was no significant differences in the gross pathology and histopathology between the post-challenge BCG and non-vaccinated groups, the enhanced pro-inflammatory immune responses observed in the post-challenge BCG group suggest caution in the use of high doses of BCG where there is a possibility that cattle may be infected with M. bovis prior to vaccination.